PENERAPAN KURIKULUM MERDEKA BELAJAR DALAM MENGEMBANGKAN MINAT BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI SISWA KELAS X SMA NEGERI 1 PUPUAN - Maheswara, Rupa; Budiasih, Ni Wayan; Muliani, Ni Made (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2023)
One of the goals of national education is the curriculum. SMA Negeri 1 Pupuan has implemented the Free Learning Curriculum policy, it needs to be studied in research so that it can be understood by Hindu Religion and Moral teachers in other schools. The issues that will be discussed include (1) What is the form of the Free Learning Curriculum in developing interest in learning Hindu Religious Education and Characteristics for class X students of SMA Negeri 1 Pupuan, (2) What are the obstacles encountered in the efforts made to overcome the obstacles to implementing the Curriculum Merdeka Learning in developing an interest in learning Hindu Religious Education and Characteristics of class X students of SMA Negeri 1 Pupuan, and (3) What are the impacts of implementing the Freedom of Learning Curriculum in developing interest in learning Hindu Religious Education and Characteristics of students of class X SMA Negeri 1 Pupuan. Theories used to analyze the problem are: Humanistic Theories, from Arthur Combs (1912-1999), Constructivistic Theories from Lorsbach and Tubin (1992). the subjects of this study were school principals, teachers of Hinduism and Hinduism students of class X SMA Negeri 1 Pupuan. The method of data collection was non-participant observation, semi-structured interviews, literature studies and documentation. The data that has been collected was analyzed using a qualitative descriptive analysis method with reduction steps, data presentation, and drawing conclusions. The results showed that the application of the independent learning curriculum in developing the learning interest of Hindu Religion Educators and the manners of class X at SMA Negeri 1 Pupuan could increase students' learning interest. It was seen that there was an increase in the courage of students in expressing ideas or ideas regarding learning materials, especially Religious Education Hinduism and Morals.